Optically pumped magnetometers reveal fasciculations non-invasively. Issue 10 (October 2021) - Marquetand, Justus; Middelmann, Thomas; Dax, Juergen; Baek, Sangyeob; Sometti, Davide; Grimm, Alexander; Lerche, Holger; Martin, Pascal; Kronlage, Cornelius; Siegel, Markus; Braun, Christoph; Broser, Philip
Highlights: First evidence that quantum sensors (optically pumped magnetometer OPM), can non-invasively detect fasciculations in neuromuscular patients. Proposal of the necessary technical solutions to detect other forms of pathological spontaneous activity. Introduction of magnetomyography as a new clinical neurophysiological diagnostic tool. Abstract: Objective: This proof-of-principle-study evaluated the extent to which spontaneous activity (SA) of the muscle can be detected via non-invasive magnetomyography (MMG) with optically pumped magnetometers (OPM). Methods: Five patients, who together exhibited all forms of SA (fibrillations, positive sharp waves, fasciculations, myotonic discharges, complex-repetitive discharges) with conventional needle electromyography (EMG), were studied by OPM-MMG and simultaneous surface EMG (sEMG) while at rest, during light muscle activation, and when a muscle stretch reflex was elicited. Three healthy subjects were measured as controls. SA was considered apparent in the OPM-MMG if a signal could be visually detected that corresponded in shape and frequency to the SA in the respective needle EMG. Results: SA in the context of fasciculations could be detected in 2 of 5 patients by simultaneous OPM-MMG/sEMG. Other forms of SA could not be detected at rest, during light muscle activation, or after provocation of a muscle stretch reflex. Conclusions: Results show that fasciculations could be detected non-invasively via a new method (OPM). Significance: We show that other forms of SA are not detectable with current OPM and propose necessary technical solutions to overcome this circumstance. Our results motivate to pursue OPM-MMG as a new clinical neurophysiological diagnostic.